Method of producing accelerated age whiskey - Meyer, Elazar (Technium: Romanian Journal of Applied Sciences and Technology, 2021)
Accelerated age whiskey having amber color, aroma and flavor similar to matured whiskey was produced in a short period of time of less than a month in comparison to at least 3 years, which is the minimal period of time needed to produce matured whiskey. A control experiment was carried out in the same manner as the method of preparing accelerated age whiskey but with use of spring water instead of beer-like liquid.